Clinical Characteristics of Patients with Antisocial Personality Disorder According to the Crime Types - Hasan KARADAG; M. Hakan TURKCAPAR; S. Olga GURIZ; Kadir OZDEL; Akfer KARAOGLAN KAHILOGULLARI (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
We aimed to evaluate the relation between the crimes committed, and the childhood behavioral problems, current clinical characteristics and anger levels of patients with antisocial personality disorder (ASPD). One hundred and fifty-three patients with ASPD were enrolled. The diagnosis was made according to the Diagnostic and Statistical Manual of Mental Disorders (DSM)-IV criteria. DSM-IV conduct disorder criteria and life history inventory was used to assess childhood characteristics. The State-Trait Anger Scale (STAS) was used to assess experience, expression, and control of anger. The main differences between crime groups were as follows: A head trauma history was more frequent in ASPD patients who had a crime history of physical assault. Loss of a parent in childhood was more frequent in individuals who committed burglary. Divorce or separation of the parents in childhood was more frequent in those who committed murder. The usage of weapons in fight during childhood was significantly higher in those who committed murder and aggravated assault. According to STAS scores, the anger control scores were significantly lower in those who committed murder. Childhood and behavioral characteristics of ASPD patients is not homogenous. There is a need for further studies to demonstrate these differences and make a new classification for ASPD. [JCBPR 2016; 5(1.000): 13-21]